Patient-Reported Outcomes after Fibula Free Flap Harvest: A Pilot Study. Issue 6 (29th November 2021) - Hatchell, Alexandra C.; Schrag, Christiaan H.; Temple-Oberle, Claire F.; Matthews, Jennifer L.; McKenzie, C. David; Matthews, T. Wayne; Chandarana, Shamir P.; Dort, Joseph C.; Baaqeel, Rasha
Abstract : Summary: Patient-reported outcomes regarding donor-site morbidity and quality of life for the fibula free flap in head and neck reconstruction patients have not been studied. The authors reviewed and identified patients who had undergone head and neck reconstruction using a fibula free flap (2011 to 2016). Patients were assessed via physical examination and two patient-reported outcomes questionnaires: the Foot and Ankle Outcome Score (score range, 0 to 100) and the Pain Disability Questionnaire (score range, 0 to 100). Quantitative data were analyzed with appropriate statistical tests. Semistructured interviews exploring donor-site challenges were performed and analyzed using thematic analysis. Seventeen patients agreed to participate. Their mean age was 62 years (range, 41 to 81 years). Mean follow-up was 38 months (range, 12 to 65 years). Mean perceived level of function compared to baseline was 67 percent. Mean scores for the Foot and Ankle Outcome Score subscales were 84.6 (pain), 80.5 (symptoms), 86.7 (activities of daily living), 67.7 (sport), and 65.6 (quality of life). The mean Pain Disability Questionnaire score was 26.3 (mild/moderate perceived disability). Higher perceived level of function was associated with higher Foot and Ankle Outcome Score values (pain, symptoms, and activities of daily living, p < 0.05). Donor limbs had decreased range of motion and manual muscle testing scores compared with their contralateral limbs ( p < 0.05). Lack of ankle support and balance, resulting in limitations and aversions to daily and sporting activities, were the most common themes regarding donor-site challenges. In conclusion, patients who have undergone fibula free flap harvest struggle with ankle support and balance and face functional difficulties that have an impact on their quality of life. Multidisciplinary approaches for targeted rehabilitation after fibula free flap harvest should be explored to determine the impact on patients' quality of life.